Treatment Outcome of Severe Acute Malnutrition Cases at the Tamale Teaching Hospital. (3rd May 2015) - Saaka, Mahama; Osman, Shaibu Mohammed; Amponsem, Anthony; Ziem, Juventus B.; Abdul-Mumin, Alhassan; Akanbong, Prosper; Yirkyio, Ernestina; Yakubu, Eliasu; Ervin, Sean
Abstract : Objective. This study investigated the treatment outcomes and determinant factors likely to be associated with recovery rate. Methods. A retrospective chart review (RCR) was performed on 348 patients who were enrolled in the outpatient care (OPC) during the study period. Results. Of the 348 cases, 33.6% recovered (having MUAC ≥ 125 mm), 49.1% defaulted, and 11.5% transferred to other OPC units to continue with treatment. There were 187 (53.7%) males and 161 (46.3%) females with severe malnutrition. The average weight gain rate was 28 g/kg/day. Controlling for other factors, patients who completed the treatment plan had 3.2 times higher probability of recovery from severe acute malnutrition (SAM) as compared to patients who defaulted (adjusted odds ratio (AOR) = 3.2, 95% CI = 1.9, 5.3, and p < 0.001 ). The children aged 24–59 months had 5.8 times higher probability of recovery from SAM as compared to children aged 6–11 months (AOR = 5.8, 95% CI = 2.5, 10.6, and p < 0.001 ). Conclusions. Cure rate was low and the default rate was quite high. Children who were diagnosed as having marasmus on admission stayed longer before recovery than their kwashiorkor counterparts. Younger children were of greater risk of nonrecovery.